Phenotypic and Proteomic Analysis of the Aspergillus fumigatus ΔPrtT, ΔXprG and ΔXprG/ΔPrtT Protease-Deficient Mutants - Shemesh, Einav; Hanf, Benjamin; Hagag, Shelly; Attias, Shani; Shadkchan, Yana; Fichtman, Boris; Harel, Amnon; Krüger, Thomas; Brakhage, Axel A.; Kniemeyer, Olaf; Osherov, Nir (Frontiers in Microbiology, 2017)
Aspergillus fumigatus is the most common opportunistic mold pathogen of humans, infecting immunocompromised patients. The fungus invades the lungs and other organs, causing severe damage. Penetration of the pulmonary epithelium is a key step in the infectious process. A. fumigatus produces extracellular proteases to degrade the host structural barriers. This study explores the role of the A. fumigatus transcription factor XprG in controlling secreted proteolytic activity and fungal virulence. We deleted xprG, alone and in combination with prtT, a transcription factor previously shown to regulate extracellular proteolysis. XprG deletion resulted in abnormal conidiogenesis and formation of lighter colored, more fragile conidia and a moderate reduction in secreted protease activity. Deletion of both xprG and prtT resulted in an additive reduction, generating a mutant strain with almost no secreted protease activity. Detailed proteomic analysis identified numerous secreted proteases regulated by XprG and PrtT, alone and in combination. Interestingly, proteomics also identified reduced levels of secreted cell wall modifying enzymes (glucanases, chitinases) and allergens following deletion of these genes, suggesting they target additional cellular processes. Surprisingly, despite the major alteration in the secretome of the XprG/PrtT null mutant, including two to five-fold reductions in the level of 24 proteases, 18 glucanases, 6 chitinases and 19 allergens, it retained wild-type virulence in murine systemic and pulmonary models of infection. This study highlights the extreme adaptability of A. fumigatus during infection based on the built-in redundancy of its virulence factors.